2022
DOI: 10.2147/ijgm.s346339
|View full text |Cite
|
Sign up to set email alerts
|

Predicting New-Onset Postoperative Atrial Fibrillation Following Isolated Coronary Artery Bypass Grafting: Development and Validation of a Novel Nomogram

Abstract: Objective To select variables associated with new-onset postoperative atrial fibrillation (POAF) following isolated coronary artery bypass grafting (CABG) and develop a nomogram for risk prediction in a Chinese population. Methods The study retrospectively enrolled 4854 consecutive patients undergoing isolated CABG from February 2018 to September 2019, they were divided into derivation cohort and validation cohort with a 3:1 ratio according to the order of operation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Therefore, we tried to remove the intraoperative information in the model, only used the preoperative information, and then remodeled it to observe the model detection efficiency. The model with 6 predictors (AUC = 0.707) had reduced power compared to the model with 7 predictors, but by including fewer variables before surgery, it achieved better predictive power than the predictive model established by Fan et al[ 14 ] Therefore, these two nomograms could identify POAF as early as possible.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, we tried to remove the intraoperative information in the model, only used the preoperative information, and then remodeled it to observe the model detection efficiency. The model with 6 predictors (AUC = 0.707) had reduced power compared to the model with 7 predictors, but by including fewer variables before surgery, it achieved better predictive power than the predictive model established by Fan et al[ 14 ] Therefore, these two nomograms could identify POAF as early as possible.…”
Section: Discussionmentioning
confidence: 95%
“…However, no nomogram was used to predict the POAF. After the start of our trial, a paper using nomograms to predict POAF was published [ 14 ]. But, Fan et al have some deficiencies [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim here is to reveal a more HATCH score and POAF score. 14,15 However, Ozsin et al 16 reported SYNTAX score II was not an independent predictor for the development of PoAF but they observed that higher SYNTAX score II was correlated with the development of PoAF.…”
Section: One Of the Most Important Problems In Studies Investigatingmentioning
confidence: 99%
“…The aim here is to reveal a more predictive factor for PoAF by assigning various scores to known risk factors according to their potency. The most commonly used ones are CHA2DS2‐VASc (Congestive heart failure, Hypertension Age [≥65 = 1 point, ≥75 = 2 points], Diabetes, and Stroke/transient ischemic attack (2 points)—vascular disease [peripheral arterial disease, previous myocardial infarction, aortic atheroma]) score, HATCH score and POAF score 14,15 . However, Ozsin et al 16 reported SYNTAX score II was not an independent predictor for the development of PoAF but they observed that higher SYNTAX score II was correlated with the development of PoAF.…”
mentioning
confidence: 99%